The recovery of high value metals from spent lithium-ion batteries. - Gobey, Katherine (Cranfield University, 2018)
Much of the modern technological world in which we live is dependent on reliable energy storage in the form of batteries, from small goods such as mobile phones, to backup power systems, and everything in between. Battery use is expected to increase considerably in the near future, and as such so will battery waste, resulting in a need for efficient, economical, and environmentally friendly processing and recycling of waste batteries and their components. This project set out to investigate a new potential method of separation of cobalt and lithium from Lithium-Ion Batteries (LIB), using sodium alginate, an anionic polysaccharide already widely harvested from multiple species of seaweed, that forms an insoluble cross link polymer with divalent cation Co²⁺, thus allowing cobalt to be easily extracted and separated from the lithium in the solution. It was found that, following creation of a cobalt ion solution using water, nitric acid, and reductant hydrogen peroxide, sodium alginate solution readily formed insoluble cobalt alginate, which can then be easily removed from the solution, allowing separation of lithium and cobalt in a simple step. With fresh sodium alginate beads added in multiple runs of 2 hours up to 93.4% of cobalt by mass was removed from the solution. Alginate added and left for up to 72 hours produced lower yields of up to 79.82% removal.
Keywords: Cobalt; recycling; reclamation; sodium alginate; batteries; extraction